2013
DOI: 10.31729/jnma.2426
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Fetal Outcome in Elective versus Emergency Cesarean Section

Abstract: Introduction: The complications of cesarean section are seen more commonly in emergency than in elective cases. The aim of this study was to find out the incidence of cesarean section in Nepal Medical College Teaching Hospital and to compare the maternal and fetal outcome in elective and emergency cesarean section. Methods: A prospective study of all the cases undergoing cesarean section in Nepal Medical College Teaching Hospital was carried out during the period of six months from Asar 2069 to Mangsir … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 0 publications
4
26
1
1
Order By: Relevance
“…The maternal and fetal outcomes of trial of VBAC in selected women with one previous Cesarean delivery for non-recurrent indications were good. Obstetricians in this area should do more to allow VBAC in women with one previous Cesarean section for non recurrent indications, correlates with other studies [20,21] Maternal and perinatal outcome of our study correlates to study done byAnupamaSuwalet al [22], they found that the overall complication rate is higher in emergency cesarean section than in elective cesarean Section, similar to our study.…”
Section: Issn-2321-127xsupporting
confidence: 91%
“…The maternal and fetal outcomes of trial of VBAC in selected women with one previous Cesarean delivery for non-recurrent indications were good. Obstetricians in this area should do more to allow VBAC in women with one previous Cesarean section for non recurrent indications, correlates with other studies [20,21] Maternal and perinatal outcome of our study correlates to study done byAnupamaSuwalet al [22], they found that the overall complication rate is higher in emergency cesarean section than in elective cesarean Section, similar to our study.…”
Section: Issn-2321-127xsupporting
confidence: 91%
“…12,16,20 Some other studies also identified previous CS as a common cause of CS. 10,22 Previous CS was the key indication of elective CS in our study as reported by Suwal et al 18 Due to lack of information about patients and some other reasons, practice trial for vaginal birth after caesarean section (VBAC) is less in Mid-Western Regional Hospital. Evidence has shown that women with history of previous CS can refuse the trial due to the complications such as scar dehiscence and rupture.…”
Section: Discussionmentioning
confidence: 66%
“…Fetal distress was the first leading indication for CS in our study accounting for 20.1% as found in other studies. 11,16,18 However, it is lower as compared to 26.25% reported by Subedi 11 and 40.2% reported by Pradhan et al 16 Many other studies also described that fetal distressis a common cause of CS. 9,12,15,19,20,22 In fact, fetal distress was found to be number one indication for emergency CS as defined by Suwal et al 18 However, the gold standard method of estimation of fetal distress -Fetal scalp PH estimation was not performed to identify fetal distress in our study.…”
Section: Discussionmentioning
confidence: 89%
“…This incidence is differently assessed d depending on the definition adopted and the time of occurrence. These hemorrhages may be due to general factors such as coagulation and hemostasis disorders or local factors of placental, uterine origin or secondary factors due to traumatic lesions [16] [17]. The causes of bleeding were dominated by uterine inertia.…”
Section: Perioperative Complicationsmentioning
confidence: 99%